Decomposing technological change at the twilight of the twentieth century: Evidence and lessons from the world’s largest innovating firms - Mendonça, S.; Fai, F. (Innovation: Organization & Management, 2007)
The present-day economy, characterised by a pattern of steady technological and organisational change, has its roots in the so-called information revolution of the late twentieth century. As this unique period of recent history recedes, the benefits of hindsight make it possible to deliver new perspectives on what really happened across industries facing rapidly mutating global competitive settings. This paper provides an analysis of the transformations that occurred in a collection of technological capabilities nurtured by industrial sectors as represented by nearly 500 of the world’s largest industrial corporations during the 1980s and 1990s. Using structural decomposition analysis it shows how industries adapted under the strain of radical shifts in the technological context with varying degrees of success.